STRATEGI PENGEMBANGAN PRODUK SUSU KEDELAI DENGAN PENENTUAN KARAKTERISTIK PRODUK - Trisna Trisna; M. Syamsul Maarif; Yandra Arkeman (JURNAL TEKNIK INDUSTRI, 2013)
The aim of this paper is to descripe how a knowledge management plays a role in thedevelopment of new products with the determining of soy milk consumer characteristics andproduct characteristics by Kano method. Knowledge is a basic in decision making for newproduct development. Analysis conducted for costomer characteristic determination bydetermining costumer atribute influence buying decision and costomer clasification. Productcharacteristic in this paper uses Kano Method. The result of analysis of product characteristicshowed that halal labeling, soybean picture in packaging, inclusion of business address, ,inclusion of nutrient information, medium sweetness level are characteristic required to newproduct development of soy milk.